“Title” And “Judiciary Power Based On Law Number 48 Of 2009” - Tedy Subrata (IHSA Institute, 2022)
Judicial Power, based on Law Number 48 of 2009, is the power of an independent state to administer justice to uphold law and justice based on Pancasila for the sake of the implementation of the Republic of Indonesia. The state judiciary implements and enforces law and justice based on Pancasila. The trial was conducted